2014
DOI: 10.1088/1367-2630/16/11/113075
|View full text |Cite
|
Sign up to set email alerts
|

Laser pulse propagation and enhanced energy coupling to fast electrons in dense plasma gradients

Abstract: Laser energy absorption to fast electrons during the interaction of an ultraintense (10 20 W cm −2 ), picosecond laser pulse with a solid is investigated, experimentally and numerically, as a function of the plasma density scale length at the irradiated surface. It is shown that there is an optimum density gradient for efficient energy coupling to electrons and that this arises due to strong selffocusing and channeling driving energy absorption over an extended length in the preformed plasma. At longer density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 30 publications
(39 reference statements)
5
25
0
Order By: Relevance
“…a relativistically-induced transparency regime, has been previously demonstrated by PIC simulations [43]. In the present paper we not only took into account the effect of the relativistically induced transparency (details of which can be found in paper [44]) on the resonance condition, but also confirmed that the L-dips originate from the region of the relativistic critical density (which is greater than the nonrelativistic critical density), as shown in the next section.…”
Section: Brief Theory Of Langmuir-wave-caused Dips In Spectral Line Psupporting
confidence: 81%
“…a relativistically-induced transparency regime, has been previously demonstrated by PIC simulations [43]. In the present paper we not only took into account the effect of the relativistically induced transparency (details of which can be found in paper [44]) on the resonance condition, but also confirmed that the L-dips originate from the region of the relativistic critical density (which is greater than the nonrelativistic critical density), as shown in the next section.…”
Section: Brief Theory Of Langmuir-wave-caused Dips In Spectral Line Psupporting
confidence: 81%
“…The intensity of the laser pulse was set to 2 Â 10 20 W cm -2 . To account for the laser propagation effects due to the expansion of the front surface, 24 the target was positioned 30 lm from the incoming laser boundary. Computationally intensive test simulations with contamination layers on both the front and rear sides, and with binary collisions enabled, show that the front surface proton layer is largely ablated and does not propagate through the Al 11þ ions.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…This can be attributed to the different density distributions of preplasma which affect the laser energy absorption and coupling to hot electrons. 28 The effects may be enhanced by the density plateau formed for thicker SF which would lead to a longer interaction length. These results verify that the use of plasma shutter in VGDF target assembly allows us to actively enhance and manipulate proton beam for applications.…”
Section: Resultsmentioning
confidence: 99%